Preeclampsia and Venous Thromboembolism: Pathophysiology and Potential Therapy - Raia-Barjat, Tiphaine; Edebiri, Osasere; Ni Ainle, Fionnuala (Frontiers in Cardiovascular Medicine, 2022)
Preeclampsia (PET) is a multisystem inflammatory disorder that represents a leading cause of feto-maternal morbidity and mortality, complicating 2–5% of all pregnancies. PET incurs an increased risk of venous thromboembolism, which is one of the leading causes of death in pregnancy and in the postpartum period. This prothrombotic phenotype is attributable to the maternal phase of PET, which is characterized by a systemic inflammatory response and coagulation activation. Research continues to be undertaken in terms of preventative measures, however, currently revolves around pharmacological low dose aspirin initiated in the first trimester of pregnancy for those with risk factors. Treatment involves antenatal corticosteroids for fetal lung development in preterm birth, parenteral magnesium sulfate for fetal neuroprotection and maternal seizure prophylaxis, and timely birth of the fetus and placenta being the only definitive treatment of PET. Patients with a venous thromboembolism (VTE) risk deemed to be >1–3% are treated with pharmacological thromboprophylaxis in the form of low molecular weight heparin. Completing each woman’s VTE risk assessment is crucial, particularly in the setting of PET, as there is also a proven associated competing hemorrhagic risk.